Multimodal imaging Gd-nanoparticles functionalized with Pittsburgh compound B or a nanobody for amyloid plaques targeting. (July 2017) - Pansieri, Jonathan; Plissonneau, Marie; Stransky-Heilkron, Nathalie; Dumoulin, Mireille; Heinrich-Balard, Laurence; Rivory, Pascaline; Morfin, Jean-François; Toth, Eva; Saraiva, Maria Joao; Allémann, Eric; Tillement, Olivier; Forge, Vincent; et al.
Aim: Gadolinium-based nanoparticles were functionalized with either the Pittsburgh compound B or a nanobody (B10AP) in order to create multimodal tools for an early diagnosis of amyloidoses.Materials & methods: The ability of the functionalized nanoparticles to target amyloid fibrils made of β-amyloid peptide, amylin or Val30Met-mutated transthyretin formed in vitro or from pathological tissues was investigated by a range of spectroscopic and biophysics techniques including fluorescence microscopy.Results: Nanoparticles functionalized by both probes efficiently interacted with the three types of amyloid fibrils, with KD values in 10 micromolar and 10 nanomolar range for, respectively, Pittsburgh compound B and B10AP nanoparticles. Moreover, they allowed the detection of amyloid deposits on pathological tissues.Conclusion: Such functionalized nanoparticles could represent promising flexible and multimodal imaging tools for the early diagnostic of amyloid diseases, in other words, Alzheimer's disease, Type 2 diabetes mellitus and the familial amyloidotic polyneuropathy.